The Influence of Liquidity, Solvency, Profitability, and Activity on Stock Price of Telecommunication Companies on IDX - Muthohhari, Abdullah Hanif; Wuryani, Eni (Nomicpedia: Journal of Economics and Business Innovation, 2023)
This research was conducted to determine simultaneously or partially the effect of liquidity, solvency, profitability, and activity on stock prices at telecommunications companies listed on the IDX in the 2019-2021 period. This research was conducted using a quantitative method using four independent variables which include liquidity represented by the current ratio, solvency represented by the debt-to-equity ratio, profitability represented by return on assets, and activity represented by total assets turnover, and used one dependent variable namely the stock price. The results obtained in this study are that simultaneously the independent variables influence the dependent variable. Partially, liquidity has a negative effect on stock prices, solvency has a positive effect on stock prices, profitability has no effect on stock prices, and activity has a positive effect on stock prices.